Plaque‐Targeted Rapamycin Spherical Nucleic Acids for Synergistic Atherosclerosis Treatment. Issue 16 (28th March 2022) - Guo, Yuanyuan; Qin, Jingcan; Zhao, Qianqian; Yang, Jiapei; Wei, Xiaoer; Huang, Yu; Xie, Miao; Zhang, Chuan; Li, Yuehua
Abstract: Atherosclerosis with unstable plaques is the dominant pathological basis of lethal cardio‐cerebrovascular diseases, which can cause acute death due to the rupture of plaques. Plaque‐targeted drug delivery to achieve promoted treatment remains the main challenge because of the systemic occurrence of atheroma. Herein, a rapamycin (RAP) spherical nucleic acid (SNA) structure, capable of specifically accumulating in plaques for synergistic atherosclerosis treatment is constructed. By designing consecutive phosphorothioate (PS) at 3' terminus of the deoxyribonucleic acid (DNA) strand, multiple hydrophobic RAPs are covalently grafted onto the PS segment to form an amphiphilic drug‐grafted DNA (RAP‐DNA), which successively self‐assembles into micellar SNA (RAP‐SNA). Moreover, the phosphodiester‐DNA segment constitutes the outer shell of RAP‐SNA, enabling further hybridization with functional siRNA (targeting lectin‐like oxidized low‐density lipoprotein receptor‐1, LOX‐1) to obtain the drug codelivered SNA (LOX‐1/RAP‐SNA). With two active ingredients inside, LOX‐1/RAP‐SNA can not only induce robust autophagy and decrease the evil apoptosis of the pathological macrophages, but also simultaneously prohibit the LOX‐1‐mediated formation of damageable foam cells, realizing the effect of synergistic therapy. As a result, the LOX‐1/RAP‐SNA significantly reduces the progression of atheroma and stabilizes the plaques, providing a new strategy for synergistically targeted atherosclerosis treatment. Abstract : By covalently drug grafting and supramolecularly self‐assembling, a rapamycin (RAP) spherical nucleic acid (RAP‐SNA) is constructed to hybridize with lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1) siRNA to obtain the drug codelivery nanoformulation (LOX‐1/RAP‐SNA), which significantly suppresses abnormal cell apoptosis by inducing robust autophagy of macrophages and simultaneously inhibits LOX‐1‐mediated foam cell formation, resulting in synergistic antiatherosclerosis efficacy.